Preventing Posttraumatic Stress Related to Sexual Assault Through Early Intervention: A Systematic Review - Dworkin, Emily R.; Schumacher, ulie A. (Trauma, violence & abuse, 2018)
Sexual assault survivors come into contact with a variety of community responders after assault, and these interactions may play an important role in mitigating distress. Given theoretical understandings of the importance of early experiences in the development of posttraumatic stress (PTS), early contact with formal systems (e.g., health care, criminal justice, social services) and informal responders (e.g., friends, family) might be particularly important in preventing PTS. However, the effectiveness of these early interventions is unclear. Understanding the key elements of early interventions, both formal and informal, that successfully prevent the development of PTS could help to improve community responses to sexual assault and ultimately promote survivor well-being. In this systematic review, we investigate the types of experiences with responders in the early aftermath of assault that are associated with PTS, the duration of effects on PTS, and the role of the timing of these responses in the development of PTS. Findings indicate that responder contact alone is not typically associated with significant differences in PTS, and there is insufficient evidence to indicate that the timing of seeking help is associated with PTS, but the quality of services provided and perceptions of interactions with certain responders appear to be associated with PTS. Although many effects were short-lived, interventions that were perceived positively may be associated with lower PTS up to a year postassault. These findings support the importance of offering best practice interventions that are perceived positively, rather than simply encouraging survivors to seek help.